Pendampingan Pengajar Meningkatkan Pembelajaran Berbasis Teknologi Informasi di SDIT Alam Sahabat Al-Qur'an Aek Kanopan - Chairul Huda; Riszki Fadillah; Hazlita; Intan Nur Fitriyani; Suerni (CV. Global Cendekia Inti, 2026)
This community service activity aimed to improve teachers' competence in developing technology-based learning materials through the use of Canva and Quizizz at SD IT Alam Sahabat Al-Qur'an Aek Kanopan. The activity employed the Participatory Action Research (PAR) approach involving 15 teachers. The implementation consisted of needs identification, program planning, material presentation, Canva and Quizizz training, hands-on practice with mentoring, and evaluation. During the activity, participants developed digital learning media using Canva and interactive learning assessments using Quizizz according to the subjects they taught. The evaluation was conducted through observation and a satisfaction questionnaire using a five-point Likert scale. The results showed that all 15 participants successfully produced learning media and digital quizzes ready for classroom implementation. The evaluation also indicated an average score of 4.81 (96.2%), categorized as Very Good, demonstrating that the mentoring program effectively enhanced teachers' digital competencies and increased their readiness to integrate technology into classroom learning. This activity is expected to encourage sustainable innovation in technology-based learning within the school environment